2022
DOI: 10.1007/s40273-022-01223-w
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Cost-Effectiveness of Biomedical, Non-Surgical HIV Prevention Interventions: A Systematic Literature Review

Abstract: Background Considerable evidence on the costs and cost-effectiveness of biomedical, non-surgical interventions to prevent human immunodeficiency virus (HIV) transmission has been generated over the last decade. This study aims to synthesize findings and identify remaining knowledge gaps to suggest future research priorities. Methods A systematic literature review was carried out in August 2020 using the MEDLINE, Embase, Global Health and EconLit databases to retrieve economic evaluations and costing studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 105 publications
(158 reference statements)
0
5
0
Order By: Relevance
“…We observed that most studies did not meet GHCC criteria, including variable cost and cost‐effectiveness outcomes and units of measure. The lower quality, inconsistencies, and lack of transparency in cost and cost‐effectiveness studies have been raised by others, but to our knowledge, this is the first study to examine the cost and cost‐effectiveness literature against real‐world operational plans and assess implementation inputs and activities with such specificity [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We observed that most studies did not meet GHCC criteria, including variable cost and cost‐effectiveness outcomes and units of measure. The lower quality, inconsistencies, and lack of transparency in cost and cost‐effectiveness studies have been raised by others, but to our knowledge, this is the first study to examine the cost and cost‐effectiveness literature against real‐world operational plans and assess implementation inputs and activities with such specificity [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…and Giddings et al. [ 32 , 33 ]. We chose 2010 because clinical trials for daily oral PrEP were underway, and many countries were already considering ways to incorporate PrEP into national HIV plans, pending proven safety and efficacy.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations